Best approximation of the functions from anisotropic Nikol’skii – Besov classes defined in R^d - Yanchenko, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish the exact-order estimates for the best approximations of the functions from anisotropic Nikol’skii – Besov classes of functions of several variables by entire functions in the Lebesgue spaces.